Long‐acting porcine ACTH stimulated salivary cortisol in the diagnosis of adrenal insufficiency. (4th August 2020) - George, Geena Susan; Jabbar, Puthiyaveettil Khadar; Jayakumari, Chellamma; John, Mathew; Mini, Malathi; Thekkumkara Surendran Nair, Anish; Das, Darvin V.; Gomez, Ramesh; Sreenath, Ravindranath; Prasad, Nandini; Nair, Abilash
Abstract: Background: Synacthen stimulated salivary cortisol has been previously evaluated and found beneficial in the diagnosis of adrenal insufficiency (AI), especially in situations with altered cortisol‐binding protein (CBG) levels. Unfortunately, Synacthen is not marketed in many parts of the world whereas porcine sequence corticotrophin (Acton Prolongatum) is readily available. This study aimed to find the diagnostic accuracy of Acton prolongatum stimulated salivary cortisol test (APSST) compared to the short synacthen test (SST). Methods: Consecutive outpatients with suspected AI underwent SST initially, followed by APSST after 3 days. For APSST, saliva was collected at 0, 60 and 120 minutes after administering 30 units Acton Prolongatum intramuscularly. Serum and salivary cortisol were estimated using electrochemiluminescence assay. (Cobas e 411, Elecsys Cortisol II kits) Results: Sixty‐seven patients with clinically suspected AI were enrolled for the study. Based on SST, 35 patients were classified as having AI [primary AI (n=19) and secondary AI (n=16)] whereas 32 had normal glucocorticoid reserve. The area under receiver operator curve of 0.99 and 0.98 was observed for salivary cortisol values at 60 and 120 minutes, respectively, for APSST. A cut‐off value of 18.5 nmol/L (0.67 µg/dL) and 29.3 nmol/L (1.06 µg/dL) at 60 and 120 minutes, respectively, had a sensitivity as well as specificity of 93%‐100% in diagnosing AI. Conclusion: Salivary cortisol estimation following stimulation using intramuscular porcine ACTH (Adrenocorticotrophic hormone) (30 units) is an economical and accurate alternative to SST in the diagnosis of AI, m and its level of 30 nmol/L or more at 2 hours confirms adrenal sufficiency.